Sustainable intensification of beef production in Colombia—Chances for product differentiation and price premiums - Charry, Andrés; Narjes, Manuel Ernesto; Enciso, Karen; Peters, Michael; Burkart, Stefan (Springer, 2019)
To promote the adoption of more sustainable cattle production systems in Colombia (mainly silvopastoral systems with improved forages), some sector stakeholders have proposed the development of differentiated, higher value beef products. However, there have been no rigorous estimations of local market potential and consumer preferences for these hypothetical products yet. On the other hand, while there are clear efforts concerning the environmental impacts of cattle production, its animal welfare implications have taken a secondary place. This research attempts to evaluate the consumer’s response to both the environmental and animal welfare aspects of more sustainable food systems by (i) determining the characteristics of a consumer segment for sustainably produced beef using contingent valuation methods and (ii) estimating the marginal willingness to pay (MWTP) for animal welfare compliance and the environmental benefits derived from sustainable intensification within the identified consumer segment, employing a Discrete Choice Experiment (DCE). In addition, the study estimates the effect of information on consumer’s MWTP for environmentally friendlier beef. Results show that consumers within the identified segment are willing to pay on average 40.2% more for beef certified with both animal welfare and eco-friendly standards, with an increase of nearly 10% after being provided with information of the sector’s environmental impacts. These findings support some of the current climate change mitigation strategies in the national cattle industry while highlighting relevant opportunities and trade-offs in the context of a developing country.